New Insights About Doxorubicin-Induced Toxicity to Cardiomyoblast-Derived H9C2 Cells and Dexrazoxane Cytoprotective Effect: Contribution of In Vitro1H-NMR Metabonomics - Dallons, Matthieu; Schepkens, Corentin; Dupuis, Aurélie; Tagliatti, Vanessa; Colet, Jean-Marie (Frontiers in Pharmacology, 2020)
Doxorubicin (DOX) is an anticancer drug widely used in oncology. The main limitation to DOX treatments though is due to the cumulative dose that may lead to cardiotoxicity. Clinically, DOX-induced cardiomyopathy develops as a progressive heart failure consecutive to a progressive loss in cardiomyocytes due to cell necrosis and apoptosis induced by DOX. For many years, the cardiac oxidative stress caused by DOX was considered as its main toxic mechanism. Therefore, several clinical trials were carried out to assess the efficacy of various antioxidants as a cardioprotective strategy. Only dexrazoxane (DEX), did significantly reduce DOX cardiotoxicity. However, since other antixodants used later on to counteract DOX cardiotoxicity were not as successful as DEX, DOX-induced oxidative stress and DEX antioxidant activity are not considered as the main feature anymore and this led the scientific world to suspect other involved mechanisms which are still unknow. The objective of the present work was to study from a metabolic point of view the side effects of DOX and the protective properties of DEX. In vitro 1H-NMR metabonomics was applied to the rat cardiomyoblastic H9C2 cell line. This strategy was used with the hope of unveiling possible new targets to cope with DOX cardiotoxicity. Another underlying goal was the validation of H9C2 in vitro model for metabolic investigations of DOX and DEX effects. For this purpose, several parameters, including oxidative stress, cell mortality and apoptosis, were measured to assess the effects of DOX and DEX alone or in combination. The metabonomic study was carried out on cellular fluids collected after either 4 or 24 hours of DOX-exposure. Under such experimental conditions, both the major adverse effects reported in patients exposed to DOX and the protective effect of DEX were demonstrated in vitro, suggesting that the H9C2 in vitro model is relevant to investigate both DOX cardiotoxicity and putative cardioprotective strategies. In addition, the metabonomics findings highlighted several metabolic pathways involved in DOX cardiotoxicity and DEX cardioprotective effects as potential metabolic targets for cardioprotection : energy metabolism, redox balance, as well as phospholipids and proteins metabolism.